"Your God is Too Small": Retracing the Origins of Conflict Between Science and Religion. Issue 1 (2nd January 2022) - Ungureanu, James C.
ABSTRACT : In this paper I reexamine the origins of John William Draper's "conflict thesis." I propose an alternative conclusion than what most historians of science have offered, one based on a synthesis of recent work, and one which treats Draper's "conflict thesis" not simply as anti-Catholic propaganda, nor as a quest for cultural dominance, nor even as anti-religious in intent. Rather, the "conflict thesis" was—and may still be—a theological response.